A simulation study on locating water trees on single core XLPE underground cables using reflectometry diagnosis techniques (2020)
This project intends to exhibit the importance of preventive maintenance as it can help reduce the causes of failure on the distribution system's components, specifically on underground cables improving the system's reliability. [1] For accomplishing this goal, two wave propagation techniques: time domain reflectometry (TDR) and frequency domain reflectometry (FDR) are evaluated on its performance on locating water-trees on cable's insulation. Water treeing is a degradation of cable's insulation due to a high level of moisture that causes a line to ground fault. The project explains the wave propagation through the cable and the changes the wave has while finding defects on the insulation. It was found that both techniques could locate the water-trees on a 500m single core XLPE cable. However, the results showed that time domain reflectometry has better accuracy than frequency domain reflectometry. Also, TDR implementation has less complexity than FDR